Eye tracking as feedback tool in physics teacher education - Schweinberger, Matthias; Watzka, Bianca; Girwidz, Raimund (Frontiers in Education, 2023)
The ability to direct pupils’ attention to relevant information during the experimental process is relevant for all science teachers. The aim of this article is to investigate the effects of training the ability of prospective physics teachers to direct attention during the presentation of experiments with eye tracking visualizations of pupils’ visual attention as a feedback tool. Many eye tracking studies in the field of learning use eye movement recordings to investigate the effectiveness of an instructional design by varying cues or the presentation format. Another important line of research relates to study the teacher’s gaze in a real classroom setting (mobile eye tracking). Here we use eye tracking in a new and innovative way: Eye tracking is used as a feedback tool for prospective teachers, showing them the effects of their verbal moderations when trying to direct their pupils’ attention. The study is based on a mixed methods approach and is designed as a single factor quasi-experiment with pre-post measurement. Pre- and post-test are identical. Prospective teachers record their verbal moderations on a “silent” experimental video. The quality of the moderation is rated by several independent physics educators. In addition, pupils’ eye movements while watching the videos are recorded using eye tracking. The resulting eye movements are used by the lecturer to give individual feedback to the prospective teachers, focusing on the ability to control attention in class. The effect of this eye tracking feedback on the prospective teachers is recorded in interviews. Between the pre-test and the post-test, the results show a significant improvement in the quality of the moderations of the videos. The results of the interviews show that the reason for this improvement is the perception of one’s own impact on the pupils’ attention through eye tracking feedback. The overall training program of moderating “silent videos” including eye tracking as a feedback tool allows for targeted training of the verbal guidance of the pupils’ attention during the presentation of experiments.